2017
DOI: 10.1186/s12936-017-1960-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of piperonyl butoxide in enhancing the efficacy of pyrethroid insecticides against resistant Anopheles gambiae s.l. in Ghana

Abstract: BackgroundMalaria vector control methods involving the use of pyrethroids remain the strategies being used against malaria vectors in Ghana. These methods include the use of long-lasting insecticidal nets and indoor residual spraying in many areas in Ghana. However, there is evidence that pyrethroid resistance is widespread in many areas in Ghana. Synergists have been shown to be useful in inhibiting the enzymes that are responsible for the development of resistance and hence enhance the insecticide susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 43 publications
9
35
1
Order By: Relevance
“…This could further explain why there were no signi cant difference in frequencies between the indoor and outdoor populations. Notably, resistance has been previously reported at varying levels to DDT and deltamethrin across all vector species in Ghana [53,56] and the neighboring countries including Benin [19], Burkina Faso [27] and Togo [57]. High frequencies of resistance loci may compromise the effectiveness of vector control in the study areas that could subsequently accentuate residual transmission [41].…”
Section: Discussionmentioning
confidence: 86%
“…This could further explain why there were no signi cant difference in frequencies between the indoor and outdoor populations. Notably, resistance has been previously reported at varying levels to DDT and deltamethrin across all vector species in Ghana [53,56] and the neighboring countries including Benin [19], Burkina Faso [27] and Togo [57]. High frequencies of resistance loci may compromise the effectiveness of vector control in the study areas that could subsequently accentuate residual transmission [41].…”
Section: Discussionmentioning
confidence: 86%
“…In An . gambiae , PBO also significantly enhanced the susceptibility to pyrethroids 38 . It should be noted that results from PBO assays must be interpreted with caution, since PBO is not entirely specific for cytochrome P450.…”
Section: Discussionmentioning
confidence: 90%
“…PBO+deltamethrin and PBO+permethrin incorporated, respectively (Ketoh et al 2018). Also, a study by Dadzie et al (2017) in Ghana, reported the role of PBO in enhancing the efficacy of pyrethroid insecticides against An. gambiae s.l.…”
Section: Discussionmentioning
confidence: 99%